„Non omnis moriar”. O nawiązaniach do antyku w hiszpańskich przekładach wierszy Wisławy Szymborskiej - Woźniak, Maria Judyta (Collectanea Philologica, 2025)
The primary objective of this article is to examine the Spanish translations of three poems by Wisława Szymborska in which the Horatian formula Non omnis moriar appears: The Rest, Autotomy, The Great Number. This well-known literary motif is open to diverse interpretations in each of the translations discussed. The analytical and interpretative remarks are an expression of a hermeneutic reading (based on the understanding of hermeneutic translation criticism by Piotr De Bończa Bukowski and Beata Piecychna), in which the adequacy of the translation in relation to the original is not the primary concern. Instead, the value of the translation as an interpretatively inspiring poetic text is emphasised.